(untitled) (Journal of Nepal Geological Society, 2016)
As in the othe parts of Nepal, the environment of the Greater Himalaya is also rpidly changing with huge impacts on glacier, glacial lakes and GLOF occurrences. This paper briefly describes the environmental changes and GLOF characteristics in Nepal Himalaya.